1995
DOI: 10.1111/j.1574-6968.1995.tb07694.x
|View full text |Cite
|
Sign up to set email alerts
|

Drastic changes in the peptidoglycan composition of penicillin resistant laboratory mutants ofStreptococcus pneumoniae

Abstract: The penicillin MIC of 2 Streptococcus pneumoniae clinical isolates was increased 100-fold (from 0.02 to 2.0 micromilligrams) and 20-fold (from 0.5 to 10.0 micromilligrams) through gradual exposure of the bacteria to increasing concentrations of penicillin in the laboratory. In both mutants the affinity of all four high molecular mass penicillin binding proteins (PBPs) for penicillin was drastically reduced accompanied by major changes in the composition of peptidoglycan as resolved by HPLC. The ratio of crossl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…On the other hand, the cell wall peptidoglycan of penicillinresistant clinical isolates contains mainly abnormal branchedstem peptides (16,40,42,43). These studies suggest that the abnormal branched-stem peptides might be the preferred substrates for penicillin-resistant PBPs in vivo (16,40,42,43). We do indeed show that R-PBP2x differed drastically from SPBP2x kinetically when it was assayed with the thioester S2d as a substrate.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…On the other hand, the cell wall peptidoglycan of penicillinresistant clinical isolates contains mainly abnormal branchedstem peptides (16,40,42,43). These studies suggest that the abnormal branched-stem peptides might be the preferred substrates for penicillin-resistant PBPs in vivo (16,40,42,43). We do indeed show that R-PBP2x differed drastically from SPBP2x kinetically when it was assayed with the thioester S2d as a substrate.…”
Section: Discussionmentioning
confidence: 48%
“…Studies have shown that the cell wall peptidoglycan composition of penicillin-resistant clinical isolates of S. pneumoniae differs significantly from that of penicillin-sensitive strains (16,40,42,43). The cell wall peptidoglycan of penicillin-sensitive strains contains a majority of monomeric and oligomeric forms of linear-stem peptides (16,40,42,43). On the other hand, the cell wall peptidoglycan of penicillinresistant clinical isolates contains mainly abnormal branchedstem peptides (16,40,42,43).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations